Partial Discharge Monitoring System on High Voltage Equipments using Electroacoustic Technique - W. M. S. W. Mahmood; Yanuar Z. Arief; Zuraimy Adzis; Nor Asiah Muhamad; Muhammad Abu Bakar Sidik; Zainuddin Nawawi (IAES Indonesia Section, 2014)
Partial discharge (PD) monitoring system is considered as one of the most promising solutions for monitoring and detecting possible faults. PD is able to diagnose faults within the system in the most fundamental and simplest way. PD monitoring and measurement of high voltage equipment substations panel and power transformers have not gained the same attention in the electrical community as compared to those of rotating machines. PD tests are conducted on-site to verify the insulation of bushings, termination box and windings. The cost of an unexpected outage may be considerably more significant for a high voltage substation panel and power transformers system than just for a single motor failure. In this research, the electroacoustic PD monitoring technique is used, which is a combination of internal PD detection and ultrasound or surface PD detection was used. The testing equipment which will be used in this research is UltraTEV Plus+ equipment from EA Technology. Result shows the transient earth voltage (TEV) PD magnitude fluctuates with time. Significant high value of PD magnitude (> 19 dB) was detected and recorded at several switchgear panel and transformer. However, for the ultrasound or surface PD, from the monitoring and measurement record, no detection of PD signal was recorded at the UltraTEV Plus+ testing equipment